Observation of moiré excitons in the twisted WS2/WS2 homostructure. Issue 34 (18th August 2022) - Wu, Biao; Zheng, Haihong; Li, Shaofei; Ding, Junnan; Zeng, Yujia; Liu, Zongwen; Liu, Yanping
Abstract : We report observed moiré excitons in the WS2 /WS2 T-HS with a twist angle of about 1.5°. Our findings offer a promising prospective for further exploration of artificial excitonic crystals and quantum emitters of TMD moiré patterns. Abstract : Moiré superlattices offer a fascinating platform for designing the properties of optical excitons. The moiré pattern can generate an ordered exciton array in space, making it possible for topological excitons and quantum emitters. Recently, evidence of moiré excitons in the twisted heterostructures of TMDs has been widely reported. However, to date, the capture and investigation of moiré excitons in the twisted homostructure (T-HS) remain elusive. Here, we report the observation of moiré excitons in the WS2 /WS2 T-HS with a twist angle of about 1.5°. The PL spectrum of the T-HS region shows many small peaks with nearly constant peak spacing, which is attributed to the reconstructed moiré potential generated by the reconstructed moiré pattern to confine the intralayer excitons, thereby forming an ordered moiré exciton array. Furthermore, we have studied the influence of temperature and laser power on the moiré excitons as well as the valley polarization of the moiré excitons. Our results provide a promising prospect for further exploration of artificial excitonic crystals and quantum emitters of TMD moiré patterns.